Emergency airway management - Benger, Jonathan; Nolan, Jerry; Clancy, Mike; Cambridge eBooks (Cambridge : Cambridge University Press, 2009)
There are few situations more challenging and stressful than airway compromise in acutely ill patients. This book describes the principles of emergency airway management outside the operating theatre, systematically leading the reader through the components of successful practice from the principles of oxygen delivery and patient assessment to rapid sequence induction of anaesthesia, tracheal intubation and the difficult and failed emergency airway. Supported by clear diagrams and algorithms, the text includes sections on a range of special circumstances and up-to-date considerations of non-invasive ventilatory support, post-intubation management and commonly used drugs. Compiled by an expert team of physicians from emergency medicine, anaesthesia and critical care, Emergency Airway Management is an invaluable resource for trainee doctors in all acute specialties who may be called upon to manage a patient's airway in an emergency situation. It is also the official course manual of the UK Training in Emergency Airway Management (TEAM) course.
Difficult and failed airway / Dermot McKeown, Tim Parke, and David Lockey -- Post intubation management and preparation for transfer / Paul Younge, David Lockey, and Alasdair Gray -- Emergency airway management in special circumstances / Patricia Weir ... [et al.] -- Non-invasive ventilatory support / Alasdair Gray, Jerry Nolan, and Carl Gwinnutt -- The interface between departments and hospitals / Jerry Nolan, Mike Clancy, and Jonathan Benger -- Audit and skills maintenance / Colin Graham.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Respiratory emergencies; Respiratory intensive care; Airway (Medicine); Electronic books